2021
DOI: 10.3390/ani12010063
|View full text |Cite
|
Sign up to set email alerts
|

Biosecurity Concept: Origins, Evolution and Perspectives

Abstract: Originally used in reference to the management of biological weapons and bio-terrorism, the term biosecurity was first used in the agricultural sector in the 1980s as “the sum of risk management practices in the defence against biological threats”. This term was then taken up in different strategic documents of different organisations, so multiple definitions and understandings co-exist. This short communication reviews the origins and evolution of the biosecurity concept and discusses the future perspectives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 9 publications
1
27
0
2
Order By: Relevance
“…The awareness of biosecurity and its underlying measures is growing, as is their great relevance for livestock production, shown by the sharp increase in publications mentioning the term BSM in the pig sector by almost a factor of five between 2011 and 2021 [ 4 ] ( Fig. 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The awareness of biosecurity and its underlying measures is growing, as is their great relevance for livestock production, shown by the sharp increase in publications mentioning the term BSM in the pig sector by almost a factor of five between 2011 and 2021 [ 4 ] ( Fig. 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…We used the definition of biosecurity as defined by the World Organization for Animal Health (OIE) and EU AHL as underlying principle to define BSM, which substitutes reducing the risk of pathogen introduction into, from, or within an animal population for internal or external biosecurity, and additionally considers pathogen spread to the surrounding environment [ 12 , 14 ]. In a bigger One Health context, Renault et al (2021) state that biosecurity should include the reduction of the probability of spread of pathogens to and between animals, plants, humans, and the environment as the biosecurity definition of the OIE may not be explicit enough in mentioning the links with public and environmental health [ 4 ]. Given our primary objective of proposing a standard definition of BSM that encompasses the underlying processes for achieving biosecurity, we aimed to keep the proposed definition as parsimonious as possible to i) provide greater clarity regarding the term and ii) to tie in with existing definitions of biosecurity itself without complicating their communication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biosecurity was originally framed around issues of national security of terrorism (Renault et al, 2021). However, recent events, such as the COVID-19 pandemic, revealed that these pathogens are not bound by international borders and are not immune to exacerbating historical developments in structural racism.…”
Section: Re-imagining Biosecurity and Biosafety Educationmentioning
confidence: 99%
“…Não se trata apenas do foco à gênese dos riscos, no controle e erradicação de agentes patógenos e riscos biológicos (REZENDE et al, 2016;SOUSA et al, 2016;RENAULT;HUMBLET;SAEGERMAN, 2021). Essas ações são apenas uma parte do processo de cuidado e promoção de saúde.…”
Section: Conceitos De Biossegurançaunclassified